2009
DOI: 10.1111/j.1365-2958.2009.06894.x
|View full text |Cite
|
Sign up to set email alerts
|

SpoIIIE and a novel type of DNA translocase, SftA, couple chromosome segregation with cell division in Bacillus subtilis

Abstract: SummaryCell division must only occur once daughter chromosomes have been fully separated. However, the initiating event of bacterial cell division, assembly of the FtsZ ring, occurs while chromosome segregation is still ongoing. We show that a two-step DNA translocase system exists in Bacillus subtilis that couples chromosome segregation and cell division. The membrane-bound DNA translocase SpoIIIE assembled very late at the division septum, and only upon entrapment of DNA, while its orthologue, SftA (YtpST), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
106
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(111 citation statements)
references
References 45 publications
4
106
1
Order By: Relevance
“…SftA translocates chromosomes before septation, while SpoIIIE comes into play postseptationally when chromosomes are trapped by the septal membrane. Like B. subtilis spoIIIE mutants, the sftA mutants had a synergistic lethal defect with an smc deletion (18). The B. subtilis sftA spoIIIE double mutant undergoes normal growth, while the defect in chromosome segregation is exacerbated significantly compared to that in both single mutants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SftA translocates chromosomes before septation, while SpoIIIE comes into play postseptationally when chromosomes are trapped by the septal membrane. Like B. subtilis spoIIIE mutants, the sftA mutants had a synergistic lethal defect with an smc deletion (18). The B. subtilis sftA spoIIIE double mutant undergoes normal growth, while the defect in chromosome segregation is exacerbated significantly compared to that in both single mutants.…”
mentioning
confidence: 99%
“…192, 2010 NOTES 4071 other factors that play more significant roles in chromosome partitioning in cocci than in rods need to be identified. Recently it has been found in B. subtilis that a second FtsK/SpoIIIE-like protein, SftA (septum-associated FtsKlike translocase of DNA), coordinates chromosome translocation to ensure maximum chromosome segregation, however, at a different stage of cell division from SpoIIIE (2,18). SftA contains the C-terminal DNA binding and ATPase domain, but instead of the N-terminal transmembrane domain in SpoIIIE, it has a soluble domain.…”
mentioning
confidence: 99%
“…As a proof of principle, we found that cells lacking the nucleoid occlusion protein Noc, which divide over unsegregated chromosomes more frequently than wild-type cells when DNA replication is blocked (77), required functional SpoIIIE for growth on agar plates only when DNA replication was repeatedly inhibited (8). One gene identified in the screen, sftA, encodes a paralog of SpoIIIE that appears to play a specialized role in promoting the efficient completion of chromosome segregation when cells divide (8,36,74).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a number of mechanisms function to ensure proper localization of the cytokinetic Z-ring and control the assembly and activity of the division machinery at the septum (1,3,24,29,46). During the late stages of cell division in Bacillus subtilis, a DNA translocase (SftA) helps ensure that chromosomes are fully segregated into daughter cells before septation is completed (8,36). Failure to properly coordinate the stages of the cell cycle can lead to aberrant division events where the septum forms over the chromosome and results in at least one daughter cell lacking a complete copy of the genome.…”
mentioning
confidence: 99%
See 1 more Smart Citation